The physiological and growth response of Petunia hybrida, Tagetes erecta, and Calendula officinalis to plant and human steroids - Mohsen Ahmadi Lashaki; Shahram Sedaghathoor; Sepideh Kalatehjari; Davood Hashemabadi (AIMS Agriculture and Food, 2018)
The application of plant hormones has been long considered in the production of the plants, but the use of a whole new set of plant growth regulators including brassinosteroids and human hormones including progesterone and estradiol has been an interesting field of study for plant researchers in recent decades. The present study aimed to explore the effect of plant and animal steroid growth regulators on growth and development of Petunia, Tagetes and Calendula. The first factor was devoted to steroid growth regulators including: No hormone, 1 mg L−1 progesterone, 1 mg L−1 estradiol, 1 mg L−1 24-epibrassinolide, and 1 mg L−1 homobrassinolide. The second factor included three ornamental plant species including Petunia hybrida, Tagetes erecta, and Calendula officinalis. The recorded traits included morphological and biochemical compounds such as catalase, peroxidase, and superoxide dismutase. It was found that the highest leaf area, chlorophyll content, and peroxidase level were obtained from the plants treated with estradiol. The application of homobrassinolide had the highest effect of carotenoid and chlorophyll contents. Among the interactions, “24-epibrassinolide × Petunia” resulted in the highest leaf area, “estradiol × Calendula” resulted in highest superoxide dismutase activity, and “estradiol × Petunia” resulted in the highest peroxidase activity. We observed the desirable impact of steroids on the studied traits. Estradiol, homobrassinolide and 24-epibrassinolide improved some traits, but no specific effect was observed for the application of progesterone. According to the results, it is recommended to apply steroid growth regulators to improve the quality and yield of the plants.